MANAJEMEN LABA DI INDONESIA: STUDI SEBUAH BIBLIOGRAPI - Edy Suprianto; Doddy Setiawan (University of Merdeka Malang, 2017)
This research tries to describe the development of earnings management research in Indonesia which is from 6 accreditation journals in Indonesia which representing 3 biggest provinces in Java island. Samples obtained from 1999 to 2016 obtained 67 articles discussing earnings management. We classify this article based on the research topics, methods and models used by the researchers. The results obtained are most of the articles on earnings management in Indonesia published in Jurnal Akuntansi Keuangan Indonesia (JAKI) and Jurnal Akuntansi dan Keuangan(JAK). Antecedent topics of earnings management is a topic that is widely studied. Analytical method and accrual modified Jones model is the most popular model used because this model is considered the most appropriate to measure the accrual of earnings management compared to other models.